Effect of Plant Growth Promoting Rhizobacteria, Bacillus safensis on Growth and Yield of Ginger (Zingiber officinale R.) Under the Mid-hill Zone of Himachal Pradesh - Smriti; Sharma, Happy Dev; Sharma, Vipin (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during kharif, April–November, 2023 in the Department of Vegetable Science, Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India to explore the potential of plant growth-promoting rhizobacteria, Bacillus safensis, on growth and yield of ginger (cv. Solan Giriganga). The trial was laid out in randomized complete block design (factorial) with 7 treatments including varying levels of phosphorus fertilizer (50%, 75% and 100% of the recommended dose) with or without Bacillus safensis along with control. Various parameters were recorded including plant height, tiller number, leaf size, rhizome yield, dry matter recovery, oleoresin content, essential oil content, soil nutrient status and nutrient uptake. Ginger yield proved to be significantly affected by combination of Bacillus safensis and 75% RDP producing the highest ginger yield of 23.27 t ha-1, maximum net returns of `Rs. 7,93,308 and benefit-cost ratio of 1.32. This study concluded that the use of Bacillus safensis in conjunction with reduced phosphorus fertilizer (37.5 kg ha-1 P2O5) is an effective strategy for enhancing ginger yield and economic returns.